Single molecule studies of acidity in heterogeneous catalysts - Sun, Xiaojiao (Kansas State University, 2013)
Amorphous silica-alumina is widely used as a solid acid catalyst for various reactions in oil refining and the petrochemical industry. The strength and the number of the acid sites in the material are most often believed to arise from the alumina atoms inserted into the silica lattice. The existence of the acidity distribution across the framework is a result of the local composition or the short-range interactions on the silica-alumina surface. Conventional techniques used to characterize silica-alumina provide effective information on the average acidity, but may not reflect the heterogeneity of surface acidity within the material. Recently, it is possible to study individual catalytic sites on solid catalysts by single molecule fluorescence microscopy with high time and space resolution. Fluorophores can be chosen that emit at different wavelengths depending on the properties of the local environment. By doping these fluorophores into a solid matrix at nanomolar concentrations, individual probe molecules can be imaged. Valuable information can be extracted by analyzing changes in the fluorescence spectrum of the guest molecules within a host matrix. In this research, silica-alumina thin films were studied with single molecule fluorescence microscopy. The samples were prepared by a sol-gel method and a wide-field fluorescence microscope was used to locate and characterize the fluorescent behaviors of pH sensitive probes. In mesoporous thin films, the ratio of the dye emission at two wavelengths provides an effective means to sense the effective pH of the microenvironment in which each molecule resides. The goal of this work was to develop methods to quantify the acidity of individual micro-environments in heterogeneous networks. Pure silica films treated with external phosphate solutions of different pH values were used to provide references of the fluorescence signals from individual dye molecules. SM emission data were obtained from mesoporous Al-Si films as a function of Al content in films ranging from 0% to 20% alumina. Histograms of the emission ratio revealed that films became more acidic with increasing Al content. The acidity on interior surfaces in zeolite pores was also of interest in this work. A microfluidic device was built to isolate the interior surface from the exterior surface. Some preliminary results showed the potential of using SM fluorescence method to study the acidic properties inside the pores of zeolite crystals.
Keywords: Catalyst characterization, Single molecule fluorescence microscopy; Single molecule fluorescence microscopy; Chemical Engineering (0542); Chemistry (0485); Engineering (0537)